Diagnostic value of platelet to high-density lipoprotein cholesterol ratio in abdominal aortic aneurysms - Du, Xiao; Xu, Jin; Zhang, Shilan; Liu, Ling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAbdominal aortic aneurysm (AAA) is a disease with a relatively high mortality risk. Currently, diagnosis of AAA predominantly depends on imaging examinations, and there is an urgent need for simple and rapid screening biomarkers. The platelet to high-density lipoprotein cholesterol ratio (PHR) is an emerging biomarker reflects systemic inflammation and hypercoagulable states in cardiovascular diseases. The aim of this study is to elucidate the clinical significance of PHR in AAA.MethodsA total of 156 patients with AAA and 113 healthy controls were enrolled. Among them, 80 patients with AAA had concomitant thrombosis. Serum samples were collected upon admission to the hospital and before treatment. The equation for PHR calculation is: PHR = [platelet (1,000 cells/µl)/HDL-C (mmol/L)]. The optimal PHR cut-off was determined via ROC analysis, and logistic regression identified AAA predictors.ResultsIn this study, PHR level in patients with AAA was significantly higher than that of control group [127.00 (109.74, 163.42) vs. 192.35 (159.08, 231.66); <0.001]. Additionally, PHR value was even higher in AAA patients with thrombosis [161.80 (135.54, 193.41) vs. 220.61 (186.49, 262.27); <0.001]. ROC curve analysis revealed that PHR had a good predictive value for diagnosis of AAA, with an area under the curve (AUC) of 0.805. When it came to the diagnosis of AAA patients with thrombosis, the AUC of PHR was 0.814. Multivariate logistic regression analysis further demonstrated that PHR was an independent predictor in AAA (OR: 1.022, 95% CI: 1.012–1.031; P < 0.001) and AAA patients with thrombosis (OR: 1.016; 95% CI: 1.007–1.024; P < 0.001).ConclusionPHR has good diagnostic value for AAA and can serve as a rapid screening indicator for its clinical diagnosis.